Hubungan Faktor Internal Dengan Kelelahan Kerja Pada Tenaga Kerja Bongkar Muat - Pratiwi, Adhinda Putri; Tenri Diah Tanri Abeng (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2023)
Manpower is a resource that has an important role in work, so it is necessary to protect workers by implementing occupational safety and health while working, in order to prevent work accidents and work-related diseases. Every job has a risk for workers to experience complaints that cause work fatigue and can cause work accidents. Port workers (TKBM) are one of the workers in the informal sector who do work manually, where this will increase the risk of work fatigue so that the risk of work accidents increases. This study aims to determine the relationship between internal factors and work fatigue among port workers in Pare-Pare. The type of research used is observational analytic with a cross sectional study design. Based on the results of the chi square test, it was found that there was a significant relationship between age (0.000), years of service (0.002), nutritional status (0.012) and exercise habits (0.008) with work fatigue. Researchers suggest that workers can maintain a healthy body by paying attention to the nutritional intake consumed and doing regular exercise